Conjunctival Resection for Mooren's Ulcer Refractory to Medical Therapy: A Case Report - Al-Noufali Mahmood; Al-Habsi Shihab; Imtiaz Mohamed; Al-Julandani Nabila; Al-Yarabi Mohammed (Journal of Ophthalmic Science, 2026)
Purpose To report a rare case of Mooren’s ulcer in a healthy young male without systemic autoimmune disease, and to highlight the effectiveness of conjunctival resection as therapy for cases unresponsive to medical management. Case report A 34-year-old immunocompetent male presented with progressive peripheral corneal ulceration in the left eye. Extensive systemic and infectious evaluations, including rheumatologic, immunologic, and microbiological testing, were unremarkable. Human leukocyte antigen genotyping was DR17(03)-negative and DQ2-positive. Rheumatological evaluation yielded no definitive systemic diagnosis. Despite immunosuppressive therapy with adjuvant medications, the epithelial defect and stromal inflammation persisted. The patient underwent conjunctival resection, resulting in marked reduction in inflammation, rapid re-epithelialization, and structural stabilization of the cornea. Histopathology of excised conjunctiva showed nonspecific inflammation without granulomatous changes, vasculitis, or neoplastic features. During follow-up, patient remained in remission with visual acuity preserved at 6/6 bilaterally and no recurrence. Conclusion Mooren’s ulcer is rare but vision-threatening. Early recognition, comprehensive evaluation, and timely surgical intervention can be vision-saving. This case highlights the role of a multidisciplinary approach and supports conjunctival resection as a useful adjunct in refractory disease. Long-term follow-up is essential.
Keywords: Mooren’s Ulcer